The Potential of Vā Part 5: Research-Informed Design - Simati-Kumar, Benita (Te Kaharoa, 2021)
The article presented is part of a series of chapters that composed an exegesis, submitted in fulfilment of the requirements for the degree of Doctor of Philosophy. The series is a narrative of discovery through practice-led research. Each article reveals its purpose and significance that leads into the next series, which then eventuate to that final design proposal. The exegesis is presented in this format, to break down the components that assisted in practice-led research. Each article can be read and unpacked on its own as a learning tool. The purpose of this edited series is for the exegesis to be more accessible and adaptable creatively to those being introduced to practice-led research. The Potential of Vā Part 5: Research-informed design, critically unpacks significant concepts. These include vā, materiality and processes, lalaga, lalava, lines of location, blended backgrounds, imagery and colour and experiments underpinning the research design. The importance of archiving Pacific indigenous artefacts is based on the importance of archiving Pacific knowledge. Sāmoan people have adapted their fa’aSāmoa in the diaspora for the advancement of their culture and people. This provides the basis for which I argue that Pacific peoples should seek out new methods to preserve their artefacts. With reference to the Lala-VĀ model, the interrelationship of family, language, genealogies, chiefly systems, religion, ceremonies and other family obligations is illustrated by the link between artefacts and other aspects of Pacific culture and tradition. The comprehensive nature of the artefacts and the stories that accompany the visual image ensure that the digital archive is all-inclusive.